'Didn't know she could shout that loud': the performance of fandom among women followers of women's golf. Issue 2 (4th March 2023) - Kitching, Niamh; Bowes, Ali; Whigham, Stuart; Bairner, Alan
ABSTRACT: While a growing body of evidence exists around women fans of men's sport, less is known about women fans' perspectives and identities in relation to women's sport, and what is known tends to focus on homogenous representations of sports fans, rather than a diversity of fan types and follower styles. Building on the authors' previous appraisals of the Solheim Cup – the biggest event in women's golf – this paper examines fan performances of women at the 2019 event in Scotland. Twenty-five white women from the UK/Europe were recruited via social media before, during and after the Solheim Cup, with online interviews taking place in the following days. Using performative sports fandom as a framework, the authors seek to examine women fan performances at a major women's sporting event. The analysis of the interviews resulted in three themes around (1) friendship, care and connection, (2) negotiated fan performances and (3) distinctive fan performances. While it must be acknowledged that this is a homogenous group of fans, it is hoped that this research will add to the understanding of the diversity and complexity of fan identities.